2019
DOI: 10.1007/978-3-030-00262-6
|View full text |Cite
|
Sign up to set email alerts
|

Handbook of Software Engineering

Abstract: As the number of cores on a chip increases, power consumed by the communication structures takes significant portion of the overall power-budget. The individual components of the SoCs will be heterogeneous in nature with widely varying functionality and communication requirements. The communication topology should possibly match communication workflows among these components. In this paper, we first propose an interconnection architecture for SoC, which uses crossroad switches to construct a dedicated communic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The improvement of methods and techniques applied to software construction culminated in the structuring of development processes, along the same lines as the processes used in traditional engineering. The term process, as adopted in this work, follows the definition given by [15], who consider a process as a systematic and organized approach to plan, coordinate and execute tasks aimed at the improvement and effectiveness of software product development. The referred authors have identified four main benefits of the adoption of formal management processes: communication, coordination, training, understanding, and improvement.…”
Section: Software Development Process Managementmentioning
confidence: 99%
“…The improvement of methods and techniques applied to software construction culminated in the structuring of development processes, along the same lines as the processes used in traditional engineering. The term process, as adopted in this work, follows the definition given by [15], who consider a process as a systematic and organized approach to plan, coordinate and execute tasks aimed at the improvement and effectiveness of software product development. The referred authors have identified four main benefits of the adoption of formal management processes: communication, coordination, training, understanding, and improvement.…”
Section: Software Development Process Managementmentioning
confidence: 99%